Association of transplant center market concentration and local organ availability with deceased donor kidney utilization. Issue 6 (7th March 2022) - Husain, Syed A.; King, Kristen L.; Cron, David C.; Neidlinger, Nikole A.; Ng, Han; Mohan, Sumit; Adler, Joel T.
Abstract : Although there is a shortage of kidneys available for transplantation, many transplantable kidneys are not procured or are discarded after procurement. We investigated whether local market competition and/or organ availability impact kidney procurement/utilization. We calculated the Herfindahl–Hirschman Index (HHI) for deceased donor kidney transplants (2015–2019) for 58 US donation service areas (DSAs) and defined 4 groups: HHI ≤ 0.32 (high competition), HHI = 0.33–0.51 (medium), HHI = 0.53–0.99 (low), and HHI = 1 (monopoly). We calculated organ availability for each DSA as the number kidneys procured per incident waitlisted candidate, grouped as: <0.42, 0.42–0.69, >0.69. Characteristics of procured organs were similar across groups. In adjusted logistic regression, the HHI group was inconsistently associated with composite export/discard (reference: high competition; medium: OR 1.16, 95% CI 1.11–1.20; low 1.01, 0.96–1.06; monopoly 1.19, 1.13–1.26) and increasing organ availability was associated with export/discard (reference: availability <0.42; 0.42–0.69: OR 1.35, 95% CI 1.30–1.40; >0.69: OR 1.83, 95% CI 1.73–1.93). When analyzing each endpoint separately, lower competition was associated with higher export and only market monopoly was weakly associated with lower discard, whereas higher organ availability was associated with export and discard. These results indicate that local organ utilization is more strongly influenced by the relative intensity of the organ shortage than by market competition between centers. Abstract : This retrospective study investigated the association of market concentration within a donation service area and local organ availability with the likelihood of local utilization of deceased donor kidneys, finding that lower competition is associated with higher export, whereas higher organ availability is associated with not only export but also discard.